1892 Cholera Epidemic and Development of Medical and Sanitary System in Tomsk Province: A Case Study of Barnaul and Biysk - K. V. Valkova; N. V. Nezhentseva; O. I. Chekryzhova (Научный диалог)
This article examines the cholera epidemic of 1892 in the cities of Barnaul and Biysk in Tomsk Province. The study draws on published materials from official statistics, as well as periodicals, publications from public organizations and research societies, and church dioceses, all of which played a significant role alongside medical institutions in combating the epidemic. The aim of this research is to analyze the activities of medical, administrative, and civic organizations in response to the acute need for medical and educational assistance during the epidemic. The results include a comparative analysis of the sanitary conditions and medical-sanitary measures implemented during the cholera outbreak in Barnaul and Biysk. The study identifies the reasons for the ineffectiveness of the epidemiological measures undertaken in Barnaul, which resulted in significantly higher morbidity and mortality rates compared to provincial averages. It emphasizes that this ineffectiveness stemmed from a critical combination of adverse factors: a surge of migrants, poor sanitary conditions, and low levels of medical care accessibility for the population. Furthermore, it is demonstrated that the analysis of the outcomes of the fight against the epidemic subsequently laid the groundwork for enhancing medical assistance and improving its availability to broader segments of society.